A 2-year prospective study on childhood acute bacterial meningitis in Tengku Ampuan Afzan Hospital, Kuantan, Pahang - JA, Wahab; AA, Fadzil; K, Zainab; AM, Affendi; Muhammad, Naznin (2000)
During a 24-month period, 21 children with acute bacterial meningitis were identified and studied. The majority of the children was from low socio-economic group and the male:female sex ratio was equal. Seventeen children (81%) were aged twelve months or below. In 15 (71.5%) of the children. Haemophilus influenzae type b was recovered, while Streptococcus pneumoniae was isolated from 4 children. Neisseria spp and Salmonella spp were identified respectively in each of the other two cases. The case fatality was four (19.0%) with nine others (42%) exhibiting neurological sequelae. Except for the Salmonella spp strain that was resistant to the cephalosporin, the rest of the bacterial species were sensitive to the commonly used antibiotics. As Haemophilus influenzae type b is still the most prevalent cause of acute bacterial meningitis, it is therefore strongly recommended that the national immunisation programme in this country should include the vaccine for it in our effort to minimise the mortality and morbidity caused by this organism.